2009
DOI: 10.1167/iovs.08-2920
|View full text |Cite
|
Sign up to set email alerts
|

A Single Intraoperative Sub-Tenon’s Capsule Injection of Triamcinolone and Ciprofloxacin in a Controlled-Release System for Cataract Surgery

Abstract: One injection of DuoCat had a therapeutic response and ocular tolerance that were equivalent to conventional eye drops in controlling inflammation after cataract surgery. (ClinicalTrials.gov number, NCT00431028.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Following a posterior 40-mg triamcinolone sub-Tenon's capsule injection, an incidence of increased IOP that was lower than expected was surprisingly observed (Paganelli et al, 2004). In our most recently study, only one eye (triamcinolone group) had an IOP that exceeded 25 mmHg, and the IOP returned to a normal level with topical antihypertensive drops (Paganelli et al, 2009). However, beyond our 28-day follow-up period, delayed onset of increased IOP must be considered.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Following a posterior 40-mg triamcinolone sub-Tenon's capsule injection, an incidence of increased IOP that was lower than expected was surprisingly observed (Paganelli et al, 2004). In our most recently study, only one eye (triamcinolone group) had an IOP that exceeded 25 mmHg, and the IOP returned to a normal level with topical antihypertensive drops (Paganelli et al, 2009). However, beyond our 28-day follow-up period, delayed onset of increased IOP must be considered.…”
Section: Introductionmentioning
confidence: 69%
“…This hinders the exploration of novel therapeutic approaches for the eye with appropriate newer molecules and better engineered drug delivery technologies. To the best of our knowledge our recently published investigations open up a new era offering the potential of no need for postoperative drops in cataract surgery (Paganelli et al, 2004;Paganelli et al, 2009;Cardillo et al, 2010). These studies gave new information and substantiated a novel and optimized antibiotic prophylaxis strategy using slow delivery technology.…”
Section: Subconjunctival Delivery Of Antibiotic In Controlled-releasementioning
confidence: 99%
See 1 more Smart Citation
“…Weber et al (11) also indicated the efficacy and safety of IND eye drops compared with ketorolac 0.5% eye drops in the management of ocular inflammation after cataract surgery. Further, anti-inflammation of CIP effects for inhibition of conjunctival bacterial flora after cataract surgery has been analyzed in a controlled-release system (10). In this study, we compared the efficacy of DEX, IND and CIP in improving AC inflammation, intra-ocular pressure and final visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that DEX, indomethacin (IND), ciprofloxacin (CIP) presented anti-inflammation activity for patients with cataract (8)(9)(10)(11). On these premises, we sought to compare anti-inflammation among DEX, IND and CIP in controlling immediate inflammation after cataract surgery in clinical treatment.…”
Section: Introductionmentioning
confidence: 99%